2018
DOI: 10.1589/jpts.30.113
|View full text |Cite
|
Sign up to set email alerts
|

Effects of visual feedback balance training on the balance and ankle instability in adult men with functional ankle instability

Abstract: [Purpose] This study examined the effects of visual feedback balance training on the balance and ankle instability in adult men with functional ankle instability. [Subjects and Methods] Twenty eight adults with functional ankle instability, divided randomly into an experimental group, which performed visual feedback balance training for 20 minutes and ankle joint exercises for 10 minutes, and a control group, which performed ankle joint exercise for 30 minutes. Exercises were completed three times a week for 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 13 publications
(14 reference statements)
1
26
0
1
Order By: Relevance
“…Lower OSI scores imply less variability of the CoP, indicating better postural control 19 . Our results support previous studies that showed better balance with visual feedback, 9,10,12 indicating beneficial effect of the additional sensory input for precise postural adjustments. Notably, there were no significant differences between groups with either VF or NVF.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Lower OSI scores imply less variability of the CoP, indicating better postural control 19 . Our results support previous studies that showed better balance with visual feedback, 9,10,12 indicating beneficial effect of the additional sensory input for precise postural adjustments. Notably, there were no significant differences between groups with either VF or NVF.…”
Section: Discussionsupporting
confidence: 92%
“…Larger frontal theta values are interpreted as an increased focused attention 13 . Thus, the increased frontal theta power with the addition of visual feedback may indicate that repetitive and constant visual stimuli induced a greater amount of neurocognitive processing in the prefrontal cortex, requiring more attention for instantaneous postural adjustment 9,10,12 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Balance ability refers to the control that coordinates the body continuously in relation to the environment (Tracey et al, 2012), which was a complex of static and dynamic balance. A degraded balance capability frequently leads to instability of the ankle joint (Mattacola and Dwyer, 2002;Nam et al, 2018). Consequently, balance exercise training is often prescribed as a treatment for improving postural control, proprioception, balance, and ankle joint stability (Ross and Guskiewicz, 2006;Wortmann and Docherty, 2013;Nam et al, 2018).…”
Section: Introductionmentioning
confidence: 99%